Comparison of electrolyte examination using ion selective electrode method on serum samples immediately and delayed 8 hours - Hardyansa Hardyansa (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2023)
Electrolytes play an essential role in the human body that can affect metabolism. Electrolyte tests that clinicians often request to assess the balance of electrolyte levels in the body are Sodium (Na), Potassium (K), and Florida (Cl) examinations. Blood electrolyte examination using serum as a specimen. Serum specimens, if delayed 8 hours after sampling, will experience bacterial development, and red blood cell shrinkage occurs so that serum squeezed out in this process will change blood electrolyte levels. The study aimed to determine the difference in blood electrolyte levels (Na, K, Cl) in the sample immediately and delayed 8 hours. This type of research is analytical research with an experimental research design, namely by conducting treatment first as a control to test changes that occur after the 8-hour delay treatment. The study samples used serum, and the data directly examined electrolyte levels in this study using the ISE (ion selective electrode) method. The collected data will be tested for normality with the Kolmogorov-Smirnov test and then analyzed using the paired test sample t-test. The results showed that blood electrolyte levels Na using immediate samples had a mean value of 138.0 mmo/L, while samples delayed 8 hours had a mean value of 138 Mmo/L. Blood electrolyte levels K immediately had an average value of 4.33 Mmo/L, while samples delayed 8 hours at an average value of 4.50 Mmo/L. Blood electrolyte levels Cl immediately had an average value of 106 Mmo/L, while the sample was delayed 8 hours with an average value of 106 Mmo/L. The conclusion was that there was no difference in sodium, potassium, and chloride levels in the sample immediately and delayed 8 hours.